Moya Moya disease presenting as Chorea: A case report - S M Saifullah Quraishi; K M Iqbal Hussain; Rajini G; Sayeeda Afzal (International Journal of Medical Research and Review, 2014)
Moya moya disease is a rare disease characterized by multiple occlusions of the cerebral circulation with an unusual net like system of collaterals. In Japanese moya moya means HAZY. The disease derives its peculiar name from the angiographic appearance of cerebral vessels in the disease that resembles a `PUFF OF SMOKE`. Ischemic insult is more common in children. Chorea is rarely noted with this disease. When a child presents with chorea, clinicians may attribute this symptom to a number of diseases. Any child with involuntary movements, moya moya disease can be a possibility.